(509) Short Term Financial Planning and the Market Equilibrium التخطيط المالي قصير الأجل وتوازن السوق - Fedorowicz, Zdzislaw (INP, 2024)
The study explores the relationship between material and monetary aspects in central economic planning, where a strict balance is typically maintained between planned supplies of goods and services and their corresponding monetary demand. This balance is not only seen in total supply and demand but also in their internal structure, linking consumer goods to the purchase funds of individuals and collective consumers, and investment goods to investment funds. However, achieving this balance may be difficult at the detailed planning stage within enterprises, where the implementation of central directives can lead to discrepancies. One key factor contributing to this difference is the variation between average and specific prices for goods and services, as enterprises base their production on specific, not average, prices set by domestic and foreign trade companies. This results in differences between the planned and actual quantities of goods produced in nominal value. Furthermore, such price differences can cause a shift in the overall equilibrium, affecting both the supply and demand dynamics. The study emphasizes that even minor discrepancies in price can lead to significant deviations between the planned and actual monetary revenues, ultimately impacting the success of central economic plans.